2015
DOI: 10.1007/s13277-015-3659-9
|View full text |Cite
|
Sign up to set email alerts
|

Lip cancer and pre-cancerous lesions harbor TP53 mutations, exhibit allelic loss at 9p, 9q, and 17p, but no BRAFV600E mutations

Abstract: Molecular mechanisms of lip squamous cell carcinoma (LSCC) and actinic cheilitis (AC) are unclear. We aimed at assessing loss of heterozygosity (LOH) and TP53 and BRAF V600E mutations in these lesions. Formalin-fixed paraffin-embedded (FFPE) samples of 17 LSCC and 16 AC were included, with additional 5 fresh LSCC genotyped for TP53 mutations. LOH was assessed by six polymorphic markers located at 9p22, 9q22, and 17p13 and correlated with cell proliferation (Ki-67) and P53 immunostaining. Direct sequencing of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“…However, more specific studies to confirm this hypothesis are required. Correa et al (23) found TP53 missense mutations in AC, including CC>TT transitions, a marker of UV damage. The loss of heterozygosity and TP53 mutations detected in AC may therefore be associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, more specific studies to confirm this hypothesis are required. Correa et al (23) found TP53 missense mutations in AC, including CC>TT transitions, a marker of UV damage. The loss of heterozygosity and TP53 mutations detected in AC may therefore be associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Tokman and colleagues investigated p16 INK4a and p53 expression in oral SCC. [20] Squamous cell carcinomas of the lip, which they investigated as a sub-group in their study, were found to manifest positive staining with p16 INK4a at a rate of 58%. [26] Similarly, in our study, 63% of cases of SCC of the lip demonstrated positive staining.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Although many studies have inspected the effect of UV light on the skin, very few studies have investigated the mechanisms of AC and SCC development. [18][19][20][21][22] Thus, it is important to understand the mechanism underlying the development of SCC. This study aims to investigate nuclear expressions of p16 INK4a , p14 ARF , and p53 in normal lip mucosa, AC, and SCC of the lip, and therefore, to determine the potential importance of these markers in early carcinogenesis, as well as their relationship with histopathological prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies conducted by Metgud et al 10 reported an increase in mean serum CRP levels (12.06+1.9 mg/l) in patients suffering from OSCC. [15][16][17][18]…”
Section: Discussionmentioning
confidence: 99%